Music Segmentation and Similarity Estimation Applied to a Gaze-Controlled Musical Interface - A. F. Camporez, Higor; M. de Freitas, Yasmin; A. L. Silva, Jair; L. Costalonga, Leandro; R. O. Rocha, Helder (Revista Vórtex, 2023)
Assistive technology, especially gaze-controlled, can promote accessibility, health care, well-being and inclusion for impaired people, including musical activities that can be supported by interfaces controlled using eye tracking. Also, the Internet growth has allowed access to a huge digital music database, which can contribute to a new form of music creation. In this paper, we propose the application of Music Information Retrieval techniques for music segmentation and similarity identification, aiming at the development of a new form of musical creation using an automatic process and the optimization algorithm Harmony Search to combine segments. These techniques for segmentation and similarity of segments were implemented in an assistive musical interface controlled by eye movement to support musical creation and well-being. The experimental results can be found in [https://bit.ly/2Zl7KSC].